Cobalt and aluminum titanate lithium phosphate composite coated high-nickel ternary positive electrode material, preparation method thereof and solid-state battery

CN122930868APending Publication Date: 2026-10-16NANTONG RESHINE NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611096601.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,此类方法中的钴包覆通常采用干法物理混合,难以在基体表面形成连续均匀的包覆层,对表面残锂的消耗效果有限;同时,后续固态电解质包覆后的烧结温度较高(通常为700℃以上),容易破坏钴包覆层的结构完整性,导致复合包覆层的协同作用无法充分发挥,制约了材料循环寿命的进一步提升

Benefits of technology

1)本发明采用二流体雾化器将硝酸钴溶液喷雾至基体表面并在100℃~140℃干燥,能够在高镍三元基体表面形成连续、均匀、致密的钴基包覆层,从而更充分地消耗表面残留锂,使正极材料的表面残锂含量显著降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930868A_ABST
    Figure CN122930868A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery cathode material, and discloses a high-nickel ternary cathode material coated with cobalt and lithium aluminum titanium phosphate and a preparation method thereof and a solid-state battery, which comprises the following steps: performing primary sintering on a lithium source and a high-nickel cathode material precursor to obtain a high-nickel ternary matrix; spraying a cobalt nitrate solution to the surface of the high-nickel ternary matrix in stirring by using a two-fluid atomizer and drying to obtain a cobalt-coated material; performing secondary sintering on the cobalt-coated material to obtain a secondary sintered material; performing dry coating on the secondary sintered material by using lithium aluminum titanium phosphate to obtain a composite coated material; performing three times of sintering on the composite coated material, and obtaining the high-nickel ternary cathode material coated with cobalt and lithium aluminum titanium phosphate through post-processing. The application can significantly reduce the residual lithium content on the surface of the cathode material, improve the specific capacity and the super-long cycle stability, and the capacity retention rate of the obtained material is more than 83.7% after 2000 cycles at 25 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating, its preparation method, and a solid-state battery. Background Technology

[0002] High-nickel ternary cathode material (LiNi) x Co y Mn z O2 (x≥0.85) has become a core cathode material for solid-state batteries due to its high specific capacity. However, existing high-nickel materials generally suffer from problems such as excessive lithium residue, severe interfacial side reactions, and easy structural collapse. Under the cycling conditions of 4.2V high voltage and 25℃ / 45℃ in all-solid-state batteries, high lithium residue will cause defects such as aggravated interfacial side reactions, gas generation, and impedance spikes, resulting in low cycle life. At the same time, the actual specific capacity and rate performance of pouch cells are also difficult to meet the requirements.

[0003] In existing technologies, lithium residue removal from high-nickel materials often involves simple water washing or high-temperature calcination, which can easily lead to uneven lithium loss from the material surface and damage to the crystal structure. Existing single coatings (Al2O3, TiO2, Li3PO4) have uneven coating layers, making it difficult to simultaneously meet the comprehensive requirements of low lithium residue, high cycle stability, and high specific capacity.

[0004] In recent years, some studies have attempted to modify high-nickel ternary materials using a two-step coating method, such as coating with a cobalt compound first and then with a solid electrolyte. However, the cobalt coating in such methods usually employs a dry physical mixing process, which makes it difficult to form a continuous and uniform coating layer on the substrate surface, resulting in limited effectiveness in consuming residual lithium on the surface. Furthermore, the subsequent sintering temperature after solid electrolyte coating is relatively high (typically above 700℃), which can easily damage the structural integrity of the cobalt coating layer, preventing the synergistic effect of the composite coating layer from being fully realized and hindering further improvements in the material's cycle life. Summary of the Invention

[0005] The purpose of this invention is to provide a high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating, its preparation method, and a solid-state battery, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a high-nickel ternary cathode material cobalt-coated with lithium aluminum titanium phosphate includes the following steps: A high-nickel ternary matrix is ​​obtained by sintering a lithium source and a high-nickel cathode material precursor in one step. Cobalt nitrate solution was sprayed onto the surface of the high-nickel ternary matrix while it was being stirred using a two-fluid atomizer, and then dried at 100℃~140℃ to obtain cobalt-coated material. The cobalt-coated material is subjected to secondary sintering at 600℃~750℃ to obtain a secondary sintered material. The secondary sintered material is dry-coated with lithium aluminum titanium phosphate to obtain a composite coated material; wherein the mass of the lithium aluminum titanium phosphate accounts for 0.9% to 2.5% of the combined mass of the secondary sintered material and the lithium aluminum titanium phosphate. The composite-coated material is sintered three times at 300℃ to 400℃ to obtain a high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating.

[0007] The mass concentration of cobalt in the cobalt nitrate solution is 0.3% to 1.0%; the speed of the high-speed mixer carrying the high-nickel ternary matrix during spraying is 500 r / min to 800 r / min.

[0008] The secondary sintering is carried out in an oxygen atmosphere, with a heating rate of 1℃ / min to 3℃ / min and a holding time of 5h to 15h.

[0009] The dry coating process includes: placing the secondary sintering material and the lithium aluminum titanium phosphate in a high-speed mixer and mixing them at a speed of 500 r / min to 1500 r / min for 5 min to 30 min.

[0010] The three sintering processes are carried out in an oxygen atmosphere, with a heating rate of 1℃ / min to 3℃ / min and a holding time of 5h to 15h.

[0011] The first sintering process includes: mixing the lithium source and the high-nickel cathode material precursor in a plow mixer for 0.5 h to 2.0 h, and then performing two-stage sintering in an oxygen atmosphere; wherein the first stage sintering temperature is 450 °C to 550 °C and the holding temperature is 4 h to 6 h; and the second stage sintering temperature is 780 °C to 860 °C and the holding temperature is 10 h to 18 h.

[0012] A high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating is prepared by the aforementioned preparation method.

[0013] An all-solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte located between the positive and negative electrodes, wherein the positive electrode comprises a high-nickel ternary positive electrode material coated with cobalt and lithium aluminum titanium phosphate composite.

[0014] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1) This invention uses a two-fluid atomizer to spray cobalt nitrate solution onto the substrate surface and dry it at 100℃~140℃, which can form a continuous, uniform and dense cobalt-based coating layer on the surface of a high-nickel ternary substrate, thereby more fully consuming the residual lithium on the surface and significantly reducing the residual lithium content on the surface of the cathode material.

[0015] 2) This invention controls the secondary sintering temperature at 600℃~750℃, ensuring a firm bond between the cobalt coating layer and the substrate while avoiding excessive sintering that could damage the crystal structure. The tertiary sintering temperature is controlled at 300℃~400℃, guaranteeing the formation of a good fast-ion conductor structure in lithium titanium aluminum phosphate while preventing damage to the cobalt inner coating layer at high temperatures, thus ensuring the integrity of the composite coating layer. This synergistic selection of a specific temperature window allows the cathode material prepared by this invention to maintain a capacity retention of up to 83.7% after 2000 cycles at 25℃, significantly outperforming conventional two-step coating techniques.

[0016] 3) This invention achieves a comprehensive improvement in low residual lithium, high specific capacity and ultra-long cycle stability through a composite process of "wet spray cobalt coating + dry LATP coating", providing an effective solution for the high-voltage and long-life application of high-nickel ternary cathode materials in solid-state batteries. Attached Figure Description

[0017] Figure 1 SEM image of the ternary cathode material prepared in Example 1; Figure 2 The image shows the SEM image of the ternary cathode material prepared in Comparative Example 1. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0019] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0020] This invention provides a high-nickel ternary cathode material cobalt and lithium aluminum titanium phosphate composite coated with the same, and a method for preparing the same, as well as a solid-state battery, comprising the following steps: Step 1: First batching and sintering.

[0021] The raw materials are mixed in a plow mixer to obtain a primary mixture, which includes a lithium source and a high-nickel cathode material precursor. A high-nickel ternary matrix is ​​obtained by sintering a mixture once and then crushing it.

[0022] The precursor is mixed with LiOH·H2O (molar ratio 1:1.03~1.07); One of the pretreatment processes includes dry mixing with a plow; the raw materials are mixed in a plow mixer for 0.5h to 2.0h.

[0023] The first sintering process specifically involves: holding at 450℃~550℃ for 4h~6h in an oxygen atmosphere → holding at 780℃~860℃ for 10h~18h → furnace cooling.

[0024] The crushing process utilizes airflow / mechanical crushing equipment to crush the sintered block material.

[0025] Step 2: Cobalt coating (wet process).

[0026] The high-nickel ternary matrix prepared in step one was sprayed with cobalt nitrate solution (Co 0.3wt%~1.0wt%) in a high-speed mixer and dried to obtain a cobalt-coated sample.

[0027] The process involves first adding the matrix into a high-speed mixer, then using a peristaltic pump to spray the prepared cobalt nitrate solution into the matrix being stirred inside the high-speed mixer via a two-fluid atomizer, and finally drying it at 100℃~140℃.

[0028] The cobalt nitrate solution is prepared by mixing cobalt nitrate hexahydrate with deionized water in a 1:1 ratio.

[0029] During spraying, the high-speed mixer rotates at a speed of 500 r / min to 800 r / min.

[0030] Step 3: Secondary sintering.

[0031] The coated material is then subjected to secondary sintering to obtain secondary sintered material.

[0032] The secondary sintered material is post-processed to obtain Co-coated high-nickel ternary cathode material.

[0033] The secondary sintering process specifically involves heating to 600℃~750℃ in an oxygen atmosphere at a heating rate of 1℃ / min~3℃ / min, and holding at that temperature for 5h~15h.

[0034] Step 4: LATP coating (dry method).

[0035] The cobalt-coated sample prepared in step two was mixed with LATP (0.9wt%~2.5wt%) in a high-speed mixer to obtain a composite-coated sample.

[0036] The high-speed mixer has a mixing speed of 500 r / min to 1500 r / min and a mixing time of 5 min to 30 min.

[0037] Step 5: Three-stage sintering.

[0038] The coated material is sintered three times to obtain a three-sintered material.

[0039] The composite-coated high-nickel ternary cathode material is obtained by post-processing the materials sintered three times.

[0040] The three-stage sintering process specifically involves: heating to 300℃~400℃ in an oxygen atmosphere at a heating rate of 1℃ / min~3℃ / min, and holding at that temperature for 5h~15h.

[0041] Step Six: Post-processing.

[0042] Post-processing includes crushing and sieving to obtain high-nickel ternary cathode material.

[0043] The composition of the high-nickel ternary cathode material obtained by this invention: Core: High-nickel ternary cathode material: LiNi x Co y Mn z O2 (x=0.85~0.92, y=0.04~0.07, z=0.04~0.08, x+y+z=1); The primary particle size is 200nm~800nm, and the particle size D50 is 8μm~15μm; Composite coating layer (total content 1.2wt%~3.5wt%); Inner layer: Cobalt-based coating (CoO / Co3O4, 0.3wt%~1.0wt%). Outer layer: Lithium aluminum titanium phosphate (Li 1.5 Al 0.5 Ti 1.5 (PO4)3, LATP, 0.9wt%~2.5wt%); Example 1 Step S1: Add nickel-cobalt-manganese precursor Ni 0.85 Co 0.10 Mn 0.05 (OH)2 and lithium source LiOH were mixed in a high-speed mixer at a molar ratio of Me:Li = 1:1.05 and sintered at 840°C for 15 hours under an oxygen atmosphere. The mixture was then pulverized and sieved to obtain the matrix material.

[0044] Step S2: Add the first coating material Co(NO3)2·6H2O to water and mix for 3 minutes to obtain the dissolved material. First, put the matrix into the high-speed mixer. Use a peristaltic pump to spray the prepared cobalt nitrate solution into the matrix being stirred in the high-speed mixer through a two-fluid atomizer. Dry at 100℃~140℃.

[0045] Step S3: The mixture is sintered in a kiln at 700°C for 10 hours under an oxygen atmosphere to form an inner coating layer on the surface of the base material, thus obtaining the intermediate material.

[0046] Step S4: The intermediate material is crushed using air jet milling to disperse each first particle into multiple second particles.

[0047] Step S5: Mix the crushed intermediate material and the second coating material LATP, wherein the second coating material accounts for 2.0 wt% of the matrix material, and sinter the mixture three times at 320°C for 12 hours in an oxygen atmosphere in a kiln, so that the second coating material forms an outer coating layer on the surface of the inner coating layer. After sintering, the mixture is sieved through a 400-mesh sieve to obtain the ternary cathode material.

[0048] Comparative Example 1: Single Co-coating Only steps (2) and (3) of Example 1 were performed without LATP coating.

[0049] Comparative Example 2: Single LATP coating The matrix is ​​directly coated with LATP and then sintered in one step with a cobalt-free inner layer.

[0050] Performance Description Figure 1 The image shows a SEM image of the secondary sintered material prepared in Example 1. Figure 2 The image shows a SEM image of the secondary sintered material prepared in Comparative Example 1. The comparison shows that the surface after high-temperature spray coating exhibits more uniform cobalt coating and a better coating effect.

[0051] Table 1 shows a comparison of performance data between the examples and comparative examples. The carbon content of the cathode materials of Example 1, Comparative Example 1, and Comparative Example 2 was measured, and coin cells were made in the same way. Then, the parameters characterizing the electrical performance were measured using methods disclosed in the prior art. As can be seen from Table 1, compared with Comparative Example 1 and Comparative Example 2, Example 1 showed a significant reduction in alkali content and a significant improvement in capacity and cycle life.

[0052] Table 1. Performance data comparison between the examples and comparative examples. .

Claims

1. A method for preparing a high-nickel ternary cathode material composite-coated with cobalt and lithium aluminum titanium phosphate, characterized in that, Includes the following steps: A high-nickel ternary matrix is ​​obtained by sintering a lithium source and a high-nickel cathode material precursor in one step. Cobalt nitrate solution was sprayed onto the surface of the high-nickel ternary matrix while it was being stirred using a two-fluid atomizer, and then dried at 100℃~140℃ to obtain cobalt-coated material. The cobalt-coated material is subjected to secondary sintering at 600℃~750℃ to obtain a secondary sintered material. The secondary sintered material is dry-coated with lithium aluminum titanium phosphate to obtain a composite coated material; wherein the mass of the lithium aluminum titanium phosphate accounts for 0.9% to 2.5% of the combined mass of the secondary sintered material and the lithium aluminum titanium phosphate. The composite-coated material is sintered three times at 300℃ to 400℃ to obtain a high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating.

2. The preparation method according to claim 1, characterized in that, The mass concentration of cobalt in the cobalt nitrate solution is 0.3% to 1.0%; the speed of the high-speed mixer carrying the high-nickel ternary matrix during spraying is 500 r / min to 800 r / min.

3. The preparation method according to claim 1, characterized in that, The secondary sintering is carried out in an oxygen atmosphere, with a heating rate of 1℃ / min to 3℃ / min and a holding time of 5h to 15h.

4. The preparation method according to claim 1, characterized in that, The dry coating process includes: placing the secondary sintering material and the lithium aluminum titanium phosphate in a high-speed mixer and mixing them at a speed of 500 r / min to 1500 r / min for 5 min to 30 min.

5. The preparation method according to claim 1, characterized in that, The three sintering processes are carried out in an oxygen atmosphere, with a heating rate of 1℃ / min to 3℃ / min and a holding time of 5h to 15h.

6. The preparation method according to claim 1, characterized in that, The first sintering process includes: mixing the lithium source and the high-nickel cathode material precursor in a plow mixer for 0.5 h to 2.0 h, and then performing two-stage sintering in an oxygen atmosphere; wherein the first stage sintering temperature is 450 °C to 550 °C and the holding temperature is 4 h to 6 h; and the second stage sintering temperature is 780 °C to 860 °C and the holding temperature is 10 h to 18 h.

7. A high-nickel ternary cathode material cobalt and lithium aluminum titanium phosphate composite coated with, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 6.

8. An all-solid-state battery, comprising a positive electrode, a negative electrode, and a solid electrolyte located between the positive and negative electrodes, characterized in that, The cathode comprises the high-nickel ternary cathode material with cobalt and lithium aluminum titanium phosphate composite coating as described in claim 7.